Uso das tecnologias de informação e comunicação no processo de socialização do idoso - Schenkel, Cristiane Carla (2009)
In order to emphasize the socializing potential of the use of Information and Communication Technology (ICT) for development of the social interaction of elderly people participating in the workshop computer linked to CREATI Passo Fundo, there was an analysis of the contemporary context in which the elderly is inserted in order to recognize the biopsychosocial aspects that interfere in their lives and in the process of human aging. So that, it was analyzed questions from the demographic and scientific-technical job, such as the elderly population increases, the mergence of a new culture called cyberspace, the reconfiguration of the process of exclusion and inclusion in digital inclusion and exclusion on the basis of technical and scientific context, the us of ICTs and the intervention of these technologies in human relations. Subsequently, we proceeded to the characterization and contextualization of the elderly before the aging process, to the asses the situation of older people in the contemporary condition of the subject of the information society and user of ICT. The data were collected through participant observation and questionnaire and for the examination of the content; we applied the technique of analysis by sociograma. Data obtained using this set of features when analyzed using concepts of Gil (1999), Bardin (2009) and Ahmed (1974), revealed details of the quantitative and qualitative changes occurring in social relations through the use of technologies by seniors who participated in the study. Among them, it was observed the improved self-esteem of older people referred by them and recognized during the development of the teaching-learning environment and quality of life of these subjects because of the established network of friends and increase the frequency of the communication process developed through ICT. It was possible to see that, initially, the elderly seeking to develop computer learning to interact with the family, but inserted into virtual network established, such contacts are expanding quantitatively. It is felt that learning to use the computer and take ownership of this knowledge; the elderly feel themselves capable, useful, social and digitally inserted, therefore feeling the necessity to keep on learning